Intermolecular Interaction of Monoethanolamine, Diethanolamine, Methyl diethanolamine, 2-Amino-2-methyl-1-propanol and Piperazine Amines in Absorption Process to Capture CO2 using Molecular Dynamic Simulation Approach - Emyra Ezzaty, Masiren; Noorlisa, Harun; Wan Hanisah, Wan Ibrahim; Fatmawati, Adam (Universiti Malaysia Pahang, 2016)
Many active researches struggle to identify a solution towards problem of effect excessive CO2 emission in atmosphere. Global warming effect happen when there has excess of CO2 percentage in atmosphere. Amine-based absorption process technology is selected in this work because their efficiency to capture CO2 up to 90%. The aim of this paper is to study intermolecular interaction of MEA, DEA, MDEA, AMP and PZ amines based absorption process to capture CO2 using molecular dynamic (MD) simulation. MD simulation was run under condition 313K and 1 atm. It used NVE ensemble at 200ps and NVT ensemble at 1ns. The results were interpreted in term of intermolecular interaction by using Radial Distribution Function (RDF) analysis. It was found that AMP solvent shows the highest tendency to make intermolecular interaction with H2O and CO2 compared to MEA, DEA, MDEA and PZ. MDEA has the weakest intermolecular interaction with CO2 among others. Thus it is required that MDEA to blend with promoter or other amine for enhance the reaction with CO2. The blend of conventional amine i.e. MEA, DEA and MDEA with activator amine is expecting to increase CO2 absorption capacity and reduce heat regeneration requirement.